2020
DOI: 10.1088/2057-1976/ab81ad
|View full text |Cite
|
Sign up to set email alerts
|

Identification and separation of rigid image registration error sources, demonstrated for MRI-only image guided radiotherapy

Abstract: Purpose: Rigid image registration (RIR) accuracy is crucial for image guided radiotherapy (IGRT). However, existing clinical image registration assessment methods cannot separate and quantify RIR error sources. Herein, we develop an extension of the 'full circle method' for RIR consistency. Paired registration circuits are used to isolate sources of RIR error caused by reference dataset substitution, from those inherent to the underlying RIR. This approach was demonstrated in the context of MRI-only IGRT, asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Our results are in line with those in the literature, whether comparing against the baseline findings from prostate studies [5][6][7][8][9][10] or the more relevant rectum study findings of Maspero [13] and Tyyger [14]. We found the systematic impact of sCT and MR on translations and rotations were <± 1 mm and <±0.5 • similarly to Maspero for sCT reference images.…”
Section: Tablesupporting
confidence: 90%
See 2 more Smart Citations
“…Our results are in line with those in the literature, whether comparing against the baseline findings from prostate studies [5][6][7][8][9][10] or the more relevant rectum study findings of Maspero [13] and Tyyger [14]. We found the systematic impact of sCT and MR on translations and rotations were <± 1 mm and <±0.5 • similarly to Maspero for sCT reference images.…”
Section: Tablesupporting
confidence: 90%
“…Their findings suggested that sCT could be utilised as a reference image for rectal CBCT registrations, with Maspero's [13] mean differences in translations and rotations when using sCT vs. CT <±1 mm and <±0.5 • respectively. However, Tyyger [14] also found in three patients' gross misregistration occurred when using the sCT and both studies had limited patient numbers, including only 3 female patients.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As an effective tool, computer-aided diagnosis plays an increasingly important role in the actual diagnosis and treatment of orthopedic diseases [ 24 ]. In order to facilitate for doctors operating or showing the effect of algorithm realization, the realization of computer-aided diagnosis technology usually needs the help of software system.…”
Section: Design Of Computer-aided Diagnosis System For Orthopedic Diseasesmentioning
confidence: 99%
“…In future, we will train PxCGAN with an increased number of our CT-MRI datasets. Another limitation is that the ground truth in image quality and geometric assessment for sMRI can have inaccuracies from a rigid image registration between CT and T2-weighted MRI as performed in the clinic (Hamdan et al 2017, Padgett et al 2018, Tyyger et al 2020. Even though the anatomical changes between the two scans are as small as possible, the bladder-filling difference might have confused the training of PxCGAN.…”
Section: Discussionmentioning
confidence: 99%